Providing Instruction Based on Students’ Learning Style Preferences Does Not Improve Learning - Rogowsky, Beth A. (Front Psychol, 2020)
Teachers commonly categorize students as visual or auditory learners. Despite a lack of empirical evidence, teaching to a student’s perceived learning style remains common practice in education (Pashler et al., 2009). Having conducted an extensive review of the literature, Pashler et al. (2009) noted, “...very few studies have even used an experimental methodology capable of testing the validity of learning styles applied to education” (p. 105). Rogowsky et al. (2015) published the first study following the experimental design prescribed by Pashler et al. Focusing specifically on the visual/auditory dichotomy, Rogowsky et al. (2015) examined the extent to which learning style predicts comprehension and retention based on mode of instruction. Their study has been noted as “The only study located through the systematic literature search across six different databases and the screening of more than 1000 records that was totally aligned with Pashler’s criteria” (Aslaksen and Loras, 2018, p. 3). The caveat to the 2015 study is that it was conducted with adult learners. The current study uses the same design and methodology as its predecessor, but on a school-aged population, making it the first of its kind. Consistent with earlier findings with adults, results failed to find a significant relationship between auditory or visual learning style preference and comprehension. Fifth graders with a visual learning style scored higher than those with an auditory learning style on listening and reading comprehension measures. As such, and counter to current educational beliefs and practices, teachers may actually be doing a disservice to students by using resources to determine their learning style and then tailoring the curriculum to match that learning style.